Modern Türk Edebiyatında Dede Algısı - Harmancı, Abdullah (Muş Alparslan Üniversitesi, 2021)
Grandfather is a factor that affects a person's life from different points of view. If a person considers himself as a result, it would not be wrong to think that the grandfather would be the cause of many things. It is unimaginable that an actor who has such a great impact on people and his life would not be reflected in the literature produced by humans in different ways. In modern Turkish literature, it is seen that the grandfather is mentioned in many literary genres and fields extending from poetry to short story, novel and children's literature.Modern life changes everything, as well as the grandfather. The positive relationships between grandchildren and grandparents change within the challenges of modern life. Grandfather was sometimes the matter of change and moved away from his family. Being without a grandfather has been the subject of many essays and short stories, poems. In the article, it will be attempted to answer the question of how the grandfather figure is mentioned in adults'literature, especially in the genres of short stories and poetry, as well as in different genres of children's literature.

Dede, bir insanın hayatında, birçok farklı açından onu etkileyen bir faktördür. İnsan kendini bir sonuç olarak görmekteyse, dedenin birçok şeyin sebebi olduğunu düşünmek yanlış olmaz. İnsana ve onun hayatına böylesine büyük etkisi olan bir aktörün gene insan tarafından üretilen edebiyata farklı biçimlerde yansımaması düşünülemez. Modern Türk edebiyatında şiirden öyküye, romana ve çocuk edebiyatına uzanan birçok edebi türde ve alanda dedenin konu edildiği görülür. Modern hayat her şeyi değiştirdiği gibi dedeyi de değiştirir. Torunla dedenin arasındaki olumlu ilişkiler, modern hayatın zorunlulukları içerisinde değişir. Dede bazen değişimin konusu olmuş ve ailesinden uzaklaşmıştır. Dedesiz olmak, birçok yazının ve öykünün, şiirin konusu haline getirilmiştir. Makalede; yetişkin edebiyatında özellikle öykü ve şiir türlerinde, ayrıca çocuk edebiyatının farklı türlerinde dede figürünün nasıl ele alındığı sorusu cevaplandırılmaya çalışılacaktır.
Perception of Grandfather in Modern Turkish Literatüre
anemon
Keywords: Modern Turkish Literature; Poetry; Short story; Children; Grandfather; Modern Türk Edebiyatı; Şiir; Öykü; Çocuk Edebiyatı; Dede